Smooth pertubations of Lorenz-like flows - Vidarte, José Humberto Bravo (2014)
Given a Geometric Lorenz Flow X on \'R POT. n+2\' of class \'C POT. k+1\'; by definition there exists a Poincaré map \'P IND. X\' of class \'C POT. k+1\'; often so-called Lorenz-type map [ABS83]. The main purpose in this dissertation is to show that under certain conditions the Lorenz-type map \'P IND.X\' can be associate to it a one-dimensional transformation \'f IND. X\' of class \'C POT. k\' (defined on an interval). This association is so-called the reduction transformation R; so we have \'RP IND. X\' = \'f IND. X\'. This association would allow us to study the dynamical properties for the original flow using techniques of one-dimensional dynamics of class \'C POT. k\'